Identifying the Antecedents for Relationship Quality Model and Its Outcomes for Priority Banking Customers in Indonesia - Syafrizal, .; Nabsiah, Abdul Wahid; Ishak, Ismail (Penerbit Universiti Sains Malaysia, 2017)
Indonesian banks have started to focus on finding the right relationship quality model to be applied to their day-to-day operation, particularly for their priority banking customers (PBC) who contribute the most to their profitable growth. This study investigates firstly, whether positive emotional expression (PEE) acts as the antecedent to relationship quality (satisfaction and trust); and secondly, whether relationship quality (RQ) leads to wordof-mouth (WOM) and share-of-purchase (SOP) as its positive outcomes. Results from a survey carried out on 338 priority banking customers in Jakarta, Indonesia found that indeed PEE acts as the antecedent to RQ while RQ is positively linked to the WOM and SOP outcomes. These findings suggest that PEE, WOM, and SOP are variables that must be considered by Indonesian banks when they strategise to enhance the relationship quality of their priority banking customers.